Generování OFDM signálů pomocí generátoru libovolných průběhů LW410 - Jagoš, Ľubomír (Vysoké učení technické v Brně. Fakulta elektrotechniky a komunikačních technologií, 2017)
Práca popisuje základné prvky OFDM modulátoru, venuje sa ich implementácií v prostredí Matlab, taktiež sa sústreďuje na použitie USRP softvérového rádia spolu s Matlabom a vytvorenie funkčného OFDM modulátoru. Pozornosť je venovaná predovšetkým praktickej implementácií na reálnom hardware.

This thesis describing basic concepts and parts of OFDM modulator, showing their implementation in Matlaba. It's also focusing on how to use USRP with Matlab and creating functional OFDM modulator. Main efford is forwarded to practical impelementation of OFDM using available hardware.
Generation of OFDM signals using arbitrary waveform generator LW410
Keywords: OFDM signál; generátor LeCroy LW410; Matlab; GUI; ifft; fft; GnuRadio; kmitočtový alokátor; ISI; ICI; OFDM signal; waveform generator LeCroy LW410; Matlab; GUI; ifft; fft; GnuRadio; carrier allocator; ISI; ICI